Nostromo - Conrad, Joseph, 1857-1924.; Warren, Robert Penn, 1905- (New York : Modern Library, 1983)
A story of capitalist exploitation and revolution and of Nostromo, the leader and foreman of the dock hands, who receives a consignment of silver. Chance and vanity make him decide to bury the silver and to pretend it was lost.
Young Adult
Young Adult
1160